ChemInform Abstract: Strain‐Promoted Retro‐Dieckmann‐Type Condensation on [2.2.2]‐ and [2.2.1]Bicyclic Systems: A Fragmentation Reaction for the Preparation of Functionalized Heterocycles and Carbocycles. Issue 6 (11th February 2014) - Moreno‐Clavijo, Elena; Moreno‐Vargas, Antonio J.; Carmona, Ana T.; Robina, Inmaculada
Abstract The ring strain of (7‐hetero)norbornene and (7‐hetero)norbornane systems is exploited in the opening of (7‐hetero)bicyclic skeletons containing a β‐ketosulfone/ester functionality through a retro‐Dieckmann type reaction.